Caring for COVID-19 patients in Malaysian ICUs: A qualitative analysis of nurses’ experiences and management dynamics - Nur Mursyidah, Abdul Hamid; Mohamad Firdaus, Mohamad Ismail; Siti Zuhaidah, Shahadan; Salizar, Mohamed Ludin; Nazri, Mohd Yusof; Tuan Sidek, Tuan Muda (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2025)
Introduction: The COVID-19 pandemic, originating in Wuhan, China, has caused global health crises, with Malaysia facing significant challenges. The first case emerged in February 2020, and by October 2022, Malaysia recorded 4,848,314 cases and 36,387 deaths. Healthcare workers, especially nurses, bear a high infection risk and elevated burnout rates. ICU nurses have relatively high physical and mental workload. Thus, this study aims to explore the intricacies of Malaysian ICU nurses’ experiences. Materials and Methods: A qualitative approach was used, and twenty ICU nurses from Sultan Ahmad Shah Medical Center @IIUM (SASMEC @IIUM) were purposively selected. Data were obtained through an individual 30-90 minutes in-depth interview. Results: The thematic analysis used has revealed one theme with six subthemes; Theme: Challenges Encountered and Emotional Response by ICU Nurses in The Care of COVID-19 Patients, Subthemes: Interpersonal and Organizational Challenges, Task-Related Challenges, Facility-Related Challenges, Health and Well-being Challenges, Infection Control Challenges and Emotional Responses. Conclusion: The study highlights the complex challenges faced by ICU nurses caring for COVID-19 patients in Malaysia, emphasizing the need for organizational support, coping strategies, communication, and collaboration. Implementing these findings can enhance the resilience and well-being of ICU nurses in times of healthcare crises, ultimately ensuring the sustainability and effectiveness of the healthcare workforce.